DESCRIPTIVE STUDY ON CONSUMER BEHAVIOR OF NON-STICK PAN USERS IN SURABAYA - Santoso, Anastasia Ariani (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2014)
The purpose of this study was to describe consumer behavior of non-stick pan users in Surabaya. This study use descriptive statistics with quantitative approach and for the method the author use convenience sampling. In this research, the authoruses the six elements of consumer behavior that includes: Who, What, Why, When, Where, and How. In this research, the number of samples is one hundred forty respondents who used non-stick pan products to answer the research problems of data processing methods used such as frequency tables, percentage bar chart, and cross tabulation.The study found that consumers of non-stick pan are majority female, with age range 20-30 years old, work as employee. They demand for high quality product and most of the consumer satisfied with the product they owned. Most of the consumer purchase the product because of the non-stick feature and they occasionally use it. The consumer buy the product in house ware / cooking ware store and supermarket. Furthermore, majority know the product from their families.